A survey of San paintings from the southern Natal Drakensberg - Steynberg, Peter John (Rhodes University, Faculty of Humanities, Department of Fine Art, 1988)
From Introduction: The study of San rock art has undergone several different phases in approach to the interpretation of art. Two approaches are currently in use. The first emphasises the art as narrative or literal representations of San life and its proponents may be called the "art for art's sake" school. Adherents to the second approach make detailed use of the San ethnography on the belief system of these people and are highly critical of the literalists because they provide no such context. The second approach has rapidly gained ascendancy and replaced the "art for art's sake" school over the last twenty years. The watershed came with the researches of Vinnicombe (1967) in the southern Drakensberg and Maggs (1967) in the Western Cape who both embarked upon programs of research which had quantification and numerical analysis at their core, so that they could present "...some objective observations on a given sample of rock paintings in a particular area..." in order to compare and contrast paintings from geographically different areas. What Vinnicombe's numerical analyses clearly showed was that the eland was the most frequently depicted antelope and that it must have played a fundamental role "...in both the economy and the rellgious beliefs of the painters...", which opened up the search for what those beliefs might be and how they could be related to the rock art itself. In order to understand what the rock art was all about it was recognised that researchers had to meaningfully contextualise the art within the social and religious framework of the artists themselves. Without the provision of such a relevant context, as many different interpretations of the paintings could be made as there were people with imaginations. Such a piecemeal approach provides a meaningless jumble of subjective fancy which tells us something about the interpreters but nothing about the rock art. It is unfortunate that the advent of this explicitly social and anthropological approach marks the end of the amateur as a serious interpreter of San rock art, for the juxtaposition of the ethnography with the rock art requires a proper training in which the intricacies of symbol and metaphor can be recognised.
Keywords: Art, San; Rock paintings -- Drakensberg Mountains; Cave paintings -- Drakensberg Mountains; Art, Prehistoric -- Drakensberg Mountains; Art, Prehistoric -- South Africa